Truth Control of Dublicate Measurings under Uncertainty Conditions - V. A. Anischenko (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2010)
The paper considers a problem pertaining to truth control of dublicate measurings of technological variables under conditions of data deficit on characteristics of measuring facilities and controlled variables.The proposed control method improves a probability to detect and identify untrue dublicate measurings.